Comparison of complications of pentavalent and DTP vaccination in infants aged 2-6 months in Anzali, Iran - Reza Sharafi (Iranian Journal of Neonatology, 2016)
Background: Despite the efforts to enhance hygiene education and personal hygiene and use of antibiotics and vaccination, infectious diseases remain the second cause of mortality worldwide. Vaccination is one of the greatest medical achievements in the prevention of mortality and morbidity, which has decreased treatment costs. This study aimed to compare the complications caused by pentavalent and diphtheria-tetanus-pertussis (DTP) vaccination in infants aged 2-6 months. Methods: This analytical cross-sectional study was conducted on all the infants aged 2-6 months referred to the healthcare centers of Anzali, Iran. Demographic data and complications of vaccination were collected from all the samples. Data analysis was performed using descriptive statistics, Fisher's exact test, Chi-square, and Mann-Whitney U test, and logistic regression analysis in SPSS. Results: In total, 353 infants, including 163 female (46.2%) and 190 male (53.8%), were enrolled in this study. According to the results, 229 infants (64.9%) presented with vaccination complications. Fewer side effects were noted in infants receiving pentavalent vaccination compared to those receiving DTP vaccination (P=0.38). In order of occurrence, the most common complications of DTP vaccination were fever, excessive crying, and fussiness, respectively. Moreover, a significant correlation was observed between the used milk by infants and the extent of complications caused by vaccination in the pentavalent group (P=0.037). Conclusion: According to the results of this study, application of pentavalent vaccination not only minimizes the local reactions, but it also diminishes local discomfort through reducing the number of injections. Therefore, infants receiving this type of vaccination encounter minimum local reactions. It is recommended that further investigation be conducted on larger sample sizes in multiple healthcare centers.